The role of mathematical experimentation in the development of creativity - Karin Ritter Jelinek (Educação Matemática Debate)
Mathematics in Brazil is still predominantly taught from the perspective of transmission of knowledge, and differentiated practices are largely scarce in the classroom. In contrast to this concept, experimentation presents itself as an innovative methodology which puts students in the center of the learning process, allowing them to create hypotheses, devise their own strategies, and develop their argumentation and creativity. Manipulatives support this process, enabling the exploration of diverse strategies and innovative solutions. From this perspective, the study sought to understand how the basic curriculum of Brazil (BNCC) and international guidance documents treat the relation between experimental activities and the development of creativity in students. To this end, a qualitative approach was adopted using documentary research to analyze the selected primary sources. The results indicate that mathematical creativity is promoted when pedagogical practices value reasoning, reflection and experimentation.